An Overview of Healthcare Systems in Comoros: The Effects of Two Decades of Political Instability - Kassim Said Mohamed (Ubiquity Press, 2021)
Background: There is ongoing scientific evidence pointing out the adverse effects of conflict on population health and development. Union of Comoros has experienced nearly two decades of political instability and military rule. This comprehensive review was carried out to ask whether the health crisis in Comoros is attributable to the consequences of the chronic political instability. Methods: This study involved a series of semi-structured interviews with key informants complemented by a comprehensive literature search of electronic databases and grey literature. A literature search was performed using all identified keywords associated with health indicators in Comoros to identify potential eligible publications in both English and French from 1975 to July 2020. Results: The analysis demonstrated that political instability and lack of proper leadership from the Government undermine the establishment of health policies which contributed dramatically to the decline in health performance. Additionally, the resurgence and emergence of old and new diseases such as cholera, chikungunya, malaria, HIV/AIDS as indicators of inadequate health services were most likely during political turmoil. Data also showed an out-migration of the health workforce and an increased overseas medical treatment demand, which indicate less attractive working conditions and weak health systems in the country. Meanwhile, an increasing performance of health status indicators was observed after the comprehensive peace process of the 2000-Fomboni Declaration. Conclusions: The chronic political instability in Comoros has contributed to the health crisis facing the Union of Comoros. It has hampered the implementation of proper institutions, which might guarantee the socio-economic development and prosperity of the population. Further studies were needed to evaluate the health burden associated with the two decades of political instability and military rule.